1998
DOI: 10.1021/om971102+
|View full text |Cite
|
Sign up to set email alerts
|

CC-Coupling Reactions of Group 6 Allenylidenes with Ynamines:  Formation of New Cyclobutenylidene and Pentatrienylidene Complexes

Abstract: The reaction of the diarylallenylidene complexes [(CO)5MCCC(C6H4R-p)2] (M = Cr (1), W (2); R = H (a), Me (b), OMe (c), NMe2 (d)) with the ynamines MeC⋮CNEt2 and PhC⋮CNEt2 affords two products:  alkenylallenylidene (3, 5) and cyclobutenylidene complexes (4, 6). The alkenylallenylidene complexes [(CO)5MCCC(NEt2)C(R‘)C(C6H4R-p)2] (R‘ = Me, M = Cr (3), W (5), R = H (a), Me (b), OMe (c), NMe2 (d); R‘ = Ph, M = Cr (3), R = OMe (e), NMe2 (f)) are formed via cycloaddition of the C⋮C bond of the ynamine to the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In contrast, from the corresponding reaction of diarylallenylidene complexes with diethylaminopropyne [14] without subsequent cycloreversion) are obtained. The product ratios strongly depend on the solvent and the substitution pattern at C c .…”
Section: Resultsmentioning
confidence: 93%
“…In contrast, from the corresponding reaction of diarylallenylidene complexes with diethylaminopropyne [14] without subsequent cycloreversion) are obtained. The product ratios strongly depend on the solvent and the substitution pattern at C c .…”
Section: Resultsmentioning
confidence: 93%
“…345 pentacarbonyl complexes with ynamines. 346 In THF solution, complex 428 slowly eliminates N 2 and rearranges to 429, which limits the utility of this method to generate pyrazolylidene complexes. 4.1.2.…”
Section: Complexes With Other 5-membered N-heterocyclic Carbene Ligandsmentioning
confidence: 99%
“…A subsequent cycloreversion reaction yields the alkenyl(amino)allenylidenes 3 and 4 . An analogous mechanism was also proposed in the cycloaddition of ynamines with Group 6 allenylidene complexes 2a…”
Section: Methodsmentioning
confidence: 65%
“…While simple nucleophilic and electrophilic additions are well‐studied, cycloaddition processes are scarce, in particular those involving CC dipolar substrates 2. In 1998 Fischer and co‐workers reported the synthesis of cyclobutenylidene and alkenylallenylidene Group 6 metal complexes which are formed as a mixture by the cycloaddition of ynamines to both the C α C β and C β C γ bonds of an allenylidene chain, respectively 2a. During our investigations into the reactivity of indenyl–allenylidene complexes [Ru(CCCR 1 R 2 )( η 5 ‐C 9 H 7 )(PPh 3 ) 2 ][PF 6 ] we have shown that the addition of nucleophiles to the unsaturated chain takes place regioselectively at the C γ .…”
Section: Methodsmentioning
confidence: 99%